Long-Term Follow-Up of Children with Congenital Diaphragmatic Hernia—Observations from a Single Institution - Koziarkiewicz, Maria; Taczalska, Anna; Piaseczna-Piotrowska, Anna (European Journal of Pediatric Surgery, 2014)
Introduction Congenital diaphragmatic hernia (CDH) is a complex malformation. The majority of children after CDH repair lead normal life, with good exercise tolerance. However, in some patients, long-term sequelae are observed, resulting from the primary defect and implemented treatment.Material and Methods We evaluated (basing on clinical examination and review of medical records) the incidence of the most common long-term complications after surgical repair of CDH and determined their risk factors. The study group comprised 50 children operated in our department for CDH.Results The following long-term complications were seen: recurrent respiratory system infections (34%), pathological gastrointestinal reflux (30%), body mass deficiency (20%), and chest deformations (40%). Parents reported most common symptoms from the gastrointestinal tract (48%) and recurring respiratory system infections (34%). Perfusion of the ipsilateral lung was significantly lower in the group of children in whom negative prognostic factors were present: patch repair, transposition of the liver up CDH, lung hypertension in echocardiography, high-frequency oscillatory ventilation (HFOV) use, prolonged artificial ventilation. In lung scintigraphy, in 70% of patients ipsilateral lung hypoplasia was found. There was a correlation between gastroesophageal reflux (GER) and early detection of CHD in prenatal studies and the presence of polyhydramnios. Patients with GER also required longer artificial ventilation and longer hospitalization. Significant body mass deficiency (below 3rd centile) was found in 20%, correlated with patch repair and HFOV. Chest deformations were more common in children who required synthetic patch repair and artificial ventilation for longer than 10 days.Conclusions The most common long-term complications observed in children after CDH repair are recurrent infections of the respiratory tract, lung hypoplasia, pathological GER, somatic growth abnormalities, and skeletal deformations. Children operated for CDH should be followed up regularly for many years by a multispecialty medical team. Diagnostics and/or follow-up of the above complications require detailed clinical examination, lung perfusion scintigraphy, spirometry, and 24-hour pH-metry.
Keywords: congenital diaphragmatic hernia; long-term complications; lung hypoplasia; gastroesophageal reflux; skeletal deformations